2022
DOI: 10.3389/fneur.2022.922528
|View full text |Cite
|
Sign up to set email alerts
|

Novel PLA2G6 Pathogenic Variants in Chinese Patients With PLA2G6-Associated Neurodegeneration

Abstract: BackgroundPLA2G6-associated neurodegeneration (PLAN) is a heterogeneous group of neurodegenerative diseases caused by biallelic PLA2G6 mutations, covering diseases such as infantile neuroaxonal dystrophy (INAD), atypical neuroaxonal dystrophy (ANAD), dystonia parkinsonism (DP), and autosomal recessive early-onset parkinsonism (AREP). The study aims to report the clinical and genetic features of a series of PLAN patients.MethodsThe clinical and radiological findings of five Chinese patients from three families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the ClinVar database, the pathogenicity of this variant is classified as pathogenic, and the corresponding disease is EOPD (Shen et al, 2019). Another variant site, c.1427 + 1G > A, is reported to be related to the INAD phenotype (Wan et al, 2022) the reports of the EOPD phenotype have been scarce. Previous investigations showed that the clinical symptoms of EOPD patients caused by only c.991G > T mutation were relatively mild with typical PD symptoms, no dystonia, and relatively slow disease progression (more than 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…In the ClinVar database, the pathogenicity of this variant is classified as pathogenic, and the corresponding disease is EOPD (Shen et al, 2019). Another variant site, c.1427 + 1G > A, is reported to be related to the INAD phenotype (Wan et al, 2022) the reports of the EOPD phenotype have been scarce. Previous investigations showed that the clinical symptoms of EOPD patients caused by only c.991G > T mutation were relatively mild with typical PD symptoms, no dystonia, and relatively slow disease progression (more than 10 years).…”
Section: Discussionmentioning
confidence: 99%
“…PLA2G6-related parkinsonism shows a fairly distinct phenotype of young onset parkinsonism/dystonia, gait/balance, and/or psychiatric/ cognitive symptoms (Magrinelli et al, 2022). Several population-specific mutations in PLA2G6 have been reported to cause Infantile neuroaxonal dystrophy and autosomal recessive Parkinsonism (Hanna Al-Shaikh et al, 2022;Wan Y et al, 2022). PLA2G6 gene-associated neurodegenerative disorders resulting from homozygous c. 2222G > A (p.Arg741Gln) mutation has been described in two cases having variable neuropsychiatric phenotypic and imaging findings from our centre (Sakhardande et al, 2021).…”
Section: Figurementioning
confidence: 99%